Beyond the Binary Equations of Sexual/Gender Experience: An Inquiry into Indonesian Selfhood and Polyversality - Hamzić, Vanja (2011)
This study presents a critical ethnographic analysis of the narratives and politics of representation of gender-variant human subjectivities in Indonesia. It interrogates, in particular, Eisenstein's concept of ‘polyversal’ personhood in relation to these phenomena.